Mathematical writing ability through Cooperative Learning with Think Talk Write (TTW) - Anisah, Anisah; Asikin, Mohammad; Hidayah, Isti (Department of Mathematics, Universitas Negeri Semarang, 2020)
The objectives of this research are to test the efectiveness of cooperative learning with TTW strategy on mathematical writing ability and to analyze mathematical writing ability of eighth grade students based on self-esteem on cooperative learning with TTW strategy. This research is a mix methode research. The population is eighth grade students of SMP Negeri 1 Jeruklegi Cilacap at the year of academic 2018/2019. The selection of quantitative samples uses cluster random sampling while the qualitative subjects uses purposive sampling. The results showed that cooperative learning with TTW strategy is effective on mathematical writing ability, and students with low self-esteem level generally have mathematical writing ability with low criteria on written text and drawing aspect and moderate on mathematical expression aspect, while students with high self-esteem level have mathematical writing ability with high criteria on all aspects.